The Investigation of Pulmonary Function Changes of COVID-19 Patients in Three Months. (17th January 2022) - Ye, Lingyan; Yao, Guifei; Lin, Shuangxiang; Fang, Yicheng; Chen, Xi; Wang, Liangxing; He, Susu
Abstract : Background . Novel coronavirus disease 2019 (COVID-19) was discovered in December 2019 and has infected more than 80 million people worldwide, and more than 50 million people have achieved a clinical cure. In this study, the pulmonary function results of patients after clinical medicine for three months were reported. Objective . To investigate the effect of COVID-19 on lung function in patients. Methods . A retrospective analysis was performed on 56 COVID-19-infected patients who were cured after the clinical treatment at Taizhou Public Health Medical Center in Zhejiang Province from January 31, 2020, to March 10, 2020. At discharge and three months after discharge, lung function was measured, including inspiratory vital capacity (IVC), forced vital capacity (FVC), forced expiratory volume in first second (FEV1), forced expiratory volume in first second to inspiratory vital capacity (FEV1/IVC), maximum mid-expiratory flow rate (MEF), peak expiratory flow rate (PEF), and carbon monoxide dispersion (DLCO). Results . At discharge, there were 37 patients (66.1%) with pulmonary dysfunction, 22 patients (39.3%) with ventilation dysfunction, 31 cases (55.4%) with small airway dysfunction, and 16 cases (28.6%) with restricted ventilation dysfunction combined with small airway dysfunction. At 3 months after discharge, 24 of the 56 patients still had pulmonary dysfunction and all of them had small airway dysfunction, of which 10 patients (17.9%) were restricted ventilation dysfunction combined with small airway dysfunction. DLCO was measured three months after discharge. Twenty-nine patients (51.8%) had mild to moderate diffuse dysfunction. All pulmonary function indexes of 56 patients recovered gradually after 3 months after release, except FEV1/IVC, and the difference was statistically significant (P < 0.05). There were 41 patients of normal type (73.2%) and 15 patients of severe type (26.8%). Among the 15 severe patients, 8 patients (53.3%) had ventilation dysfunction at discharge, 9 patients (60%) had small airway dysfunction, 4 patients (26.7%) still had ventilation dysfunction 3 months after discharge, 7 patients (46.7%) had small airway dysfunction, and 10 patients (66.7%) had diffuse dysfunction. Among the 41 common type patients, 14 patients (34.1%) had ventilation dysfunction at discharge, 22 patients (53.7%) had small airway dysfunction, 6 patients (14.6%) still had ventilation dysfunction 3 months after discharge, 17 patients (41.5%) had small airway dysfunction, and 19 patients (46.3%) had diffuse dysfunction. Patients with severe COVID-19 had more pulmonary impairment and improved pulmonary function than normal patients. Conclusion . COVID-19 infection can cause lung function impairment, manifested as restricted ventilation dysfunction, small airway dysfunction, and diffuse dysfunction. The pulmonary function of most patients was improved 3 months after clinical cure and discharge, and some patients remained with mild to moderate diffuse dysfunction and small airway dysfunction.